The moderating role of corporate governance on tax incentives and real investments - Mohamad Faizuddin Alimon; Anna Che Azmi; Mohd Zulkhairi Mustapha (Penerbit Universiti Kebangsaan Malaysia, 2023)
Tax incentives have extensively been employed to promote real investment in the manufacturing sector. This study unravels reservations about investment tax incentives and real investment’s positive relationship with corporate governance moderation over the study period of 2001 to 2015. It is further supported that although specific investment tax incentives of PS and RA exhibit a positive relationship with real investment, ITA displays a negative relationship with real investment, and the interactions of corporate governance have consistent negative relationships with real investment. This study recommends the recognition of the importance of corporate governance as an integral part of investment tax incentives and real investment establishment.